Analysis Contribution of Sectoral and Human Development Index to the Poverty Rate in Bengkulu Province - Tiara Sela; Retno A. Ekaputri (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
This study aims to determine the Sectoral Contribution and Human Development Index (HDI) to the Poverty rate in North Bengkulu Regency, Rejang Lebong Regency, Bengkulu City, and Bengkulu Province in 2013-2022. Data compiled from secondary data on BPS publications. Firstly, an analysis was conducted on 17 Sectors' Contributions to the total economy in the area, calculated for North Bengkulu Regency, Rejang Lebong Regency, Bengkulu City, and Bengkulu Province. Secondly, analysis by panel data regression method to find the highest Contribution Sector and HDI to Poverty rate. Results indicated that (1) The highest sectoral contribution during the 2013-2022 period is the Agriculture, Forestry, and Fisheries Sector ranging from 34% to 30%. (2) The highest sector contribution and Human Development Index (HDI) simultaneously affect the poverty rate in Bengkulu Province. Furthermore, the contribution of the Agriculture, Forestry and Fisheries sectors has a significant negative effect while the Human Development Index (HDI) has a significant positive effect on the poverty rate in Bengkulu Province in 2013-2022.